Early stent thrombosis in patient after Percutaneous Coronary Intervention (PCI): A Case Report - Andreas Willianto; Martin Hendrata (PT. Kalbe Farma Tbk., 2017)
Stent thrombosis is a rare complication but have around 15-45% case fatality rate. Early stent thrombosis in first 24 hours after PCI still accounts for 6-25% from all stent thrombosis cases.This article will discuss a 60 year-old male brought to emergency with chest pain, shortness of breath and diaphoresis. The chest pain was started 1.5 hours prior to admission felt as a heavy sensation in the chest. The patient has a history of diabetes, hypertension and dyslipidemia. One week prior to admission, 2 drug eluting stent (DES) on proximal left anterior descending (LAD) and distal left circumflex (LCx) were placed. Clopidogrel and aspirin were consumed routinely as an antiplatelet. The patient diagnosed with early stent thrombosis and cardiogenic shock. Coronary artery bypass graft surgery with 4 grafts was successfully done the day after, intra-aortic balloon pump and temporary pacemaker were reserved until 2 days post-surgery. Clopidogrel was shifted to ticagrelor post-surgery and combined with aspirin. No event of subsequent acute coronary syndrome was observed.Trombosis stent merupakan komplikasi yang jarang namun angka kematiannya tinggi hingga 15-45%. Kasus trombosis stent dini dalam 24 jam pertama setelah PCI merupakan 6-25% kasus trombosis stent. Dalam artikel ini akan dibahas seorang laki-laki 60 tahun yang dibawa ke ruang gawat darurat dengan nyeri dada, sesak napas dan keringat dingin. Nyeri sejak 1,5 jam sebelum masuk rumah sakit terasa sebagai sensasi berat di dada. Pasien memiliki riwayat diabetes, hipertensi dan dislipidemia. Satu minggu sebelumnya, telah dilakukan pemasangan stent berlapis obat (DES) di proximal left anterior descending (LAD) dan distal left circumflex (LCx). Clopidogrel dan aspirin sebagai antiplatelet dikonsumsi rutin. Pasien didiagnosis trombosis stent dini dan syok kardiogenik. Operasi bedah pintas koroner jantung (CABG) dengan 4 graft dilakukan 1 hari kemudian, IABP dan alat pacu jantung sementara dipasang dan dipertahankan selama 2 hari setelah operasi. Clopidogrel diganti dengan ticagrelor setelah operasi dan dikombinasikan dengan aspirin. Setelah itu tidak ada lagi kejadian sindrom koroner akut.